Evaluation of Palliative Care Patient Outcomes From the Perspectives of Patients, Family Caregivers, and Nurses - Simge Çoşkun Palaz; Birgül Cerit (Sağlık Bilimleri Dergisi, 2026)
This descriptive, cross-sectional, and comparative study was conducted to examine differences in Palliative Care Outcomes Scale total scores among hospitalized palliative care patients, their caregivers, and nurses providing care. The study included 53 patients receiving treatment in palliative care units of two public hospitals, 53 caregivers, and 53 nurses. Data were collected using a Personal Information Form and the Palliative Care Outcomes Scale, which assesses patients’ physical, emotional, psychological, spiritual, informational, and support needs. Descriptive statistics and one-way analysis of variance were used for data analysis. The mean Palliative Care Outcomes Scale total scores were 14.83±7.01 for patients, 13.55±8.02 for caregivers, and 16.60±7.22 for nurses. No statistically significant difference was found among the three groups (F=2.260; p>0.05). The findings indicate that total Palliative Care Outcomes Scale scores were comparable across respondent groups. These results suggest consistency in the assessment of palliative care needs among patients, caregivers, and nurses, emphasizing the importance of multidisciplinary alignment in palliative care practice.